Research of Pathogenesis and Novel Therapeutics in Arthritis - Tang, Chih-Hsin (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Arthritis has a high prevalence globally and includes over 100 different types, the most common of which are rheumatoid arthritis, osteoarthritis, psoriatic arthritis, and inflammatory arthritis. The exact etiology of arthritis remains unclear and no cure exists. Anti-inflammatory drugs are commonly used in the treatment of arthritis but are associated with significant side effects. Novel modes of therapy and additional prognostic biomarkers are urgently needed for arthritis patients. This book summarizes and discusses the global picture of the current understanding of arthritis.